1980
DOI: 10.1680/geot.1980.30.3.269
|View full text |Cite
|
Sign up to set email alerts
|

A study of vibratory driving in granular soils

Abstract: Two types of vibratory pile driving have been identified by the Authors termed respectively ‘slow’ and ‘fast’ vibrodriving. The occurrence of slow or fast motion is determined by the initial soil density, pile diameter, displacement amplitude and acceleration of vibration. Slow vibrodriving is concluded to be the most widely encountered and the paper, therefore, concentrates on this type of motion. A theory and interactive computer simulation of the case of slow vibratory driving has been developed. The motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…There is now substantial support for the existence of acoustic fluidization both from engineering practice, such as vibratory pile driving [ Rodger and Littlejohn , 1980], as well as from shake tables [ Richards et al , 1990] and the response of factory foundations to strongly vibrating machinery [ Barkan , 1962]. Recent numerical simulations of large‐scale landslides [ Campbell et al , 1995], which predict fluid‐like behavior of the avalanche, appear to exhibit violent pressure fluctuations within the avalanche.…”
Section: Acoustic Fluidizationmentioning
confidence: 99%
“…There is now substantial support for the existence of acoustic fluidization both from engineering practice, such as vibratory pile driving [ Rodger and Littlejohn , 1980], as well as from shake tables [ Richards et al , 1990] and the response of factory foundations to strongly vibrating machinery [ Barkan , 1962]. Recent numerical simulations of large‐scale landslides [ Campbell et al , 1995], which predict fluid‐like behavior of the avalanche, appear to exhibit violent pressure fluctuations within the avalanche.…”
Section: Acoustic Fluidizationmentioning
confidence: 99%
“…The system is studied experimentally by Nguyen et al [17]. Studies by Barkan [18] and Rodger et al [19] revealed that vibro-impact systems produce a combination of vibration and impact and are able to achieve better soil penetration. The main aim of this paper is to identify the qualitative motion most suitable for the forward progression of the mechanism against resistive forces such as friction and soil resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Weitere wissenschaftliche Arbeiten befassen sich mit den bodenmechanischen Prozessen im zu verdichtenden Boden. Insbesondere sind die Arbeiten von Rodger und Littlejohn sowie Denies et al hervorzuheben.…”
Section: Tiefenrüttler Als Messwerkzeugunclassified